Manajemen Pesantren dalam Meningkatkan Kegiatan Keagamaan di Pondok Pesantren Al-Manar Pengasih Kulon Progo - Tajkiatu Zahra; Bunga Amarilis Rizky Mauludy; Anas Tri Ridlo Dina Yuliana; Fadlurrahman Fadlurrahman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Pesantren has an important role in the formation of the religious character of students. Pesantren Al-Manar as one of the Islamic educational institutions has developed various management strategies to analyze how the management of Pesantren Al-Manar manages the learning process, security activities, and moral development of students in order to create a generation of faith and piety. The research method used is descriptive qualitative with a case study approach at Pesantren Al-Manar. The results of the study show that effective pesantren management includes planning, implementation, supervision, and evaluation which contributes significantly to improving the religiousness of students.